Pengaruh Tingkat Pengangguran Terbuka, Tingkat Pendidikan, Dan Layanan Kesehatan Terhadap Kesejahteraan Masyarakat Dikabupaten Provinsi Banten Periode 2017-2024 : The Influence of Open Unemployment Rate, Education Level, and Health Services on Community Welfare in Banten Province Regency for the Period 2017-2024 - Tamami (Universitas Bojonegoro, 2025)
This study aims to measure the welfare of the community in the Regency in Banten Province, namely Lebak, Serang, Pandeglang, Tangerang. This type of research is quantitative research. By measuring the influence of the variables Unemployment Rate, Education Level and Health Services on Community Welfare measured by the Human Development Index (HDI) in an effort by a region to reduce poverty and manage the economy better. This study uses secondary data taken from the Banten Central Statistics Agency and the data used is annual data from 2019 to 2024 with a total of 32 observations, through Panel Data regression analysis with the help of the Eviews 12.0 computer program. The results of the study show partially that the Open Unemployment Rate (TPT) variable has a negative effect on community welfare (H1: accepted), Education Level has a positive effect (H2: accepted), and Health Services have a negative effect on community welfare (H3: rejected). Simultaneously or together the dependent variable has a positive effect on the independent variable (H4: accepted). This finding emphasizes the importance of strengthening the foundation of education policy transformation, as well as the creation of productive jobs, the addition of affordable health service infrastructure in order to improve the welfare of people at the rural level in order to increase more inclusive economic growth.